(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
Some aspects of the work of Simone de Beauvoir have been passed over in favour of her work on the position of women and her relationship with Jean-Paul Sartre. One of these aspects is the subject of this paper: her writing on human development. This paper reviews her writing on human development, which as well as broadening her relevance to psychology and psychotherapy in general, can also be thought of as unifying all her work and providing a stimulus for further research and application to existential therapeutic practice.